GIS-BASED MODELING AND FORECASTING DANGEROUS HYDROMETEOROLOGICAL PHENOMENA IN THE URAL REGION KNOWN AS URALSKOE PRIKAMYE - Pyankov, S.V.; Kalinin, N.A.; Sviyazov, E.M.; Shikhov, A.N. (Perm Federal Research Centre Journal, 2017)
The article describes the main results of an RFBR-supported research project, in the field of GIS- based modeling and forecasting hazardous hydrometeorological phenomena in the Ural region known as Uralskoe Prikamye. The main result of research is the creation of the first regional atlas of hydrometeorological hazards. The basic features of this atlas are singled out and the approaches to the creation of climatic maps of the studied region are described. We consider two approaches to creating maps of regime parameters of dangerous weather phenomena. The results of the application of long-term satellite data for the study of spatial and temporal distribution of drought, forest fires and severe forest windthrows are also presented. The database of dangerous weather phenomena, developed within the project, in the Ural Prikamye region is briefly considered. Finally, the list of publications, presenting the main results of research, is shown.